Ethnicity and Neighbourhoods: Looking Backward, Facing Forward - Zucchi, John (Urban History Review / Revue d'histoire urbaine, 2010)
Robert Harney was the most important influence on the history of urban ethnicity in Canada. We will examine how Harney and those who worked closely with him approached this phenomenon in the exciting period of the 1970s and 1980s. The second half of the article acknowledges the recent interest in immigrants, ethnicity, and the urban setting and suggests new avenues of research in this area.